Dangers of workplace bullying: evidence from the Caribbean. Issue 1 (9th January 2017) - Devonish, Dwayne
Abstract : Purpose: The purpose of this paper is to examine whether person-related bullying, work-related bullying, and physically intimidating bullying predict three forms of job strain: physical exhaustion, work-related depression, and interpersonal counterproductive work behaviour (CWB-P). Design/methodology/approach: The study surveyed a wide cross-section of employees across a number of private sector organisations in a small developing country in the Caribbean region. Findings: The prevalence rate of workplace bullying in the current Caribbean sample was 54 per cent. The regression results revealed that person-related bullying and work-related were positively related to work-related depression, whereas physically intimidating bullying and work-related bullying were positively related to CWB-P. None of the three forms of bullying predicted physical exhaustion. When the overall workplace bullying composite was used, all three job strains were significantly predicted. Research limitations/implications: The study utilised a cross-sectional self-report survey research design which does not permit causal inferences to be made. Common method variance is a possible limitation due to the use of self-report measure but this was ruled out by a Harman's single factor test. Longitudinal research using a mixture of subjective and objective measures is needed to further investigate these relationships reported here. Practical implications: First, social and interpersonal skills and emotional intelligence training and development opportunities should be provided to both managers and employees as a means of developing individuals who are socially aware, interpersonally competent, and emotionally intelligent in their interactions with each other at work. Second, a zero-tolerance approach should be communicated throughout the organisation evidenced by clear and explicit organisational policies against these acts. Third, it would be of good practical value to establish health and safety committees to identify, assess and tackle various psychosocial and other hazards at work (e.g. workplace bullying). Originality/value: The study utilised a three-dimensional model of bullying at work (as well as a composite form of bullying) for predicting three forms of job strains among employees in various Caribbean workplaces.